Knowledge required for the nurse to work in the oncological intensive care unit - Danelia Gómez Torres; María Carmen Gómez-Martínez (Universidade Federal de Santa Maria, 2018)
Aim: to determinate the nurse's knowledge in order to work in the Intensive Care Unit. Method: qualitative study carried out with seven social actors, based on Candela's theory of competences; the multiple case study method was used, supported by an interview guide and a data capture card; such instruments were validated by experts in the area. Data collection was from september to december 2016, then the analysis were made from January to February 2017. Results: the most important transcendences were classified into categories, such as: respiratory, cardiovascular, central nervous, integumentary, immunological and electrolyte system, as well as the information related to the limitation of therapeutic effort and cytotoxic drugs. Final considerations: to offer optimal care to their patients, the nursing professionals require experience related to the therapeutic limits, thanatology, palliative care and spiritual orientation of the end-stage cancer patient.